Pre-existingmental health disorders affect pregnancy and neonatal outcomes: a retrospectivecohort study - Kotryna Sūdžiūtė; Greta Murauskienė; Kristina Jarienė; Algirdas Jaras; Meilė Minkauskienė; Virginija Adomaitienė; Irena Nedzelskienė (BMC, 2020)
Abstract Background This was a hospital registry-based retrospective age-matched cohort study that aimed to compare pregnancy and neonatal outcomes of women with pre-existing mental disorders with those of mentally healthy women. Methods A matched cohort retrospective study was carried out in the Department of Obstetrics and Gynecology, Hospital of Lithuanian University of Health Sciences Kauno Klinikos, a tertiary health care institution. Medical records of pregnant women who gave birth from 2006 to 2015 were used. The study group was comprised of 131 pregnant women with mental disorders matched to 228 mentally healthy controls. The primary outcomes assessed were antenatal care characteristics; secondary outcomes were neonatal complications. Results Pregnant women with pre-existing mental health disorders were significantly more likely to have low education, be unmarried and unemployed, have a disability that led to lower working capacity, smoke more frequently, have chronic concomitant diseases, attend fewer antenatal visits, gain less weight, be hospitalized during pregnancy, spend more time in hospital during the postpartum period, and were less likely to breastfeed their newborns. The newborns of women with pre-existing mental disorders were small for gestational age (SGA) more often than those of healthy controls (12.9% vs. 7.6%, p < 0.05). No difference was found comparing the methods of delivery. Conclusions Women with pre-existing mental health disorders had a worse course of pregnancy. Mental illness increased the risk to deliver a SGA newborn (RR 2.055, 95% CI 1.081-3.908).